2015
DOI: 10.1016/j.seizure.2015.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of endothelin B receptor improves the efficacy of levetiracetam in chronic epileptic rats

Abstract: To the best of our knowledge, these findings are the first indications of the role of ETB receptor in pharmacoresistant epilepsy. Therefore, the present data suggest that the regulation of the ETB receptor-mediated signaling pathway may be important for identification of new therapeutic strategies for improving antiepileptic drug efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…Therefore, administration of the p38 MAPK inhibitor SB203580 significantly decreased the duration of the first seizure and the Racine scores in rats. These results are consistent with data from previous studies that showed that SB203580 can significantly reduce seizure intensity in a rat model of refractory epilepsy and decrease seizure duration in a rat model of chronic epilepsy ( 18 , 24 ).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, administration of the p38 MAPK inhibitor SB203580 significantly decreased the duration of the first seizure and the Racine scores in rats. These results are consistent with data from previous studies that showed that SB203580 can significantly reduce seizure intensity in a rat model of refractory epilepsy and decrease seizure duration in a rat model of chronic epilepsy ( 18 , 24 ).…”
Section: Discussionsupporting
confidence: 93%
“…Animals were video-monitored 8 h a day for general behavior and occurrence of spontaneous seizures by 6 weeks after SE. Rats showing spontaneous recurrent seizures were used as chronic epilepsy animals ( Ko and Kang, 2015 ; Kim et al, 2017c ).…”
Section: Methodsmentioning
confidence: 99%
“…Animals were video-monitored 8 h a day, for general behavior and occurrence of spontaneous seizures by 6 weeks after SE. Rats showing spontaneous recurrent seizures were used as epileptic animals [5,41,42].…”
Section: Epileptic Rat Modelmentioning
confidence: 99%
“…We applied a modified protocol for the effect of PDI knockdown on spontaneous seizure activity in epileptic rats, based on our previous reports [5,42]. Epileptic rats were anesthetized with Isoflurane (3% induction, 1.5%-2% for surgery and 1.5% maintenance in a 65:35 mixture of N2O:O2).…”
Section: Pdi Knockdown and Analysis Of Chronic Seizure Activitymentioning
confidence: 99%